A carbon horse race: Abatement subsidies vs. permit trading in Switzerland - Beat Hintermann; Maja Žarković (University of Basel, Center of Business and Economics (WWZ), 2020)
Swiss climate policy consists of three regulatory instruments for greenhouse gas emissions reduction: A CO 2 levy, the Swiss Emissions Trading System (CH EHS), and an additional nonEHS" program for medium-sized plants that consists of command-and-control elements plus a sizeable abatement subsidy. Our paper informs about this tripartite climate policy, which is unique in the international context. Second, we estimate the dierential impact of the CH EHS and the nonEHS program on plants' emissions. Our empirical strategy exploits a policy change in 2013 that instituted a mandatory emissions trading system for a subset of previously regulated rms. We nd that the nonEHS outperforms the CH EHS for a minority of plants, but that on average, the two programs result in similar abatement eorts despite very dierent nancial incentives. Firms that previously engaged in abatement eorts continue to do so even after the nancial incentives were reduced by an order of magnitude. Our results suggest the presence of preferences for abatement per se, above and beyond nancial incentives. They further imply that expanding the nonEHS system at the expense of the CO 2 levy may be associated with signifcant costs but no additional emission reductions.
Keywords: D22; D62; H23; H25; H32; Q52; Q54; Q58; 330; Climate policy; emissions tax; carbon tax; emissions trading; subsidies; command-and-control; Switzerland